Temporary restorative treatment in children and adolescents with amelogenesis imperfecta: Scoping review (2023)
Background: Amelogenesis imperfecta (AI) is a group of disorders that affect the enamel of the teeth, either in quality or quantity.This alteration causes sensitivity and is associated with factors that could affect the strength of the adhesive